Extract of limonium gmelinii attenuates AB-and H2O2-induced oxidative response in cerebral endothelial cells - Shayakhmetov, Y.; Jaguparov, A.; Tsoy, A. (Nazarbayev University, 2014)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder which affects approximately 10% of the population at age 65 and 40% of people over the age 80. Clinically, AD pathology is characterized by an increased deposition of amyloid-(3 peptide (A(3) in the brain, and a progressive impairment of cognition and memory of affected individuals. Blood Brain Barrier (BBB) dysfunction is observed in all of the stages of AD, and may even precede neuron degeneration in AD brains. During the early stages of AD, microvasculature deficiencies and hypertrophy of astrocytes are commonly observed. Numerous in vivo and in vitro studies have demonstrated that the vascular deposition of A(3 induces oxidative stress in cerebral endothelial cells (CECs). A(3-induced oxidative stress in cells, in turn, initiates a cascade of redox reactions leading to apoptosis and neurovascular inflammation. Consequently, antioxidants are considered as therapeutic agents in A(3-induced CECs damage.
Keywords: limoniun gmelinii; polyphenols; neuron; hypertrophy; astrocytes; pathology; blood brain barrier